Super (a,d)-mathcalH-Antimagic Total Covering of Amalgamation Graph K_4 and W_4 - Anggraeni, Novri; Dafik, Dafik (Prosiding Seminar Matematika dan Pendidikan Matematik, 2014)
A graph G(V,E) has a mathcalH-covering if every edge in E belongs to a subgraph of G isomorphic to mathcalH. An (a,d)-mathcalH-antimagic total covering is a total labeling lambda from V(G)cup E(G) onto the integers 1,2,3,...,|V(G)cup E(G)| with the property that, for every subgraph A of G isomorphic to mathcalH the sumA=sum_vinV(A)lambda(v)+sum_einE(A)lambda(e) forms an arithmetic sequence. A graph that admits such a labeling is called an (a,d)-mathcalH-antimagic total covering. In addition, if lambda(v)_vinV=1,...,|V|, then the graph is called mathcalH-super antimagic graph. In this paper we study of amalgamasi graph K_4 and W_4.